(untitled) (Malaysian Management Journal, 2004)
This paper defines electronic reading (e-reading) and then continues to discuss the diverse definitions of the main resource of e-reading, which are, electronic books (e-books). It then proceeds to describe the formats and standards of existing e-book initiatives, which are gaining wider interest since the introduction of portable electronic reading devices and software-based readers that provide users with a more realistic book reading experience. Advantages, disadvantages, and problems with paper-based reading are also explained. In addition, a study concerning an evaluation of e-reading satisfaction is described. Three different e-book formats (LIT, PDF, and HTML) were utilised to accomplish the primary aims of the study, which were to identify the most preferred format, associated software-based reader (Microsoft Reader, Adobe Acrobat Reader, Internet Explorer), and the potential of e-reading in the workplace. Based on a proposed preferred index, the results seem to suggest that Microsoft Reader is more preferable when compared to the other two. However, most participants preferred reading on paper rather than on screen. Although this was the case, some participants would e-read depending on resources and situations.